2011
DOI: 10.3109/17477166.2010.533774
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, fitness and metabolic risk in children: A cross-sectional and longitudinal study

Abstract: isrctn.org 15360785.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
4
14
0
1
Order By: Relevance
“…Therefore, the precise role of CRP in the development of CVD risk factors in humans remains unknown. In our study, CRP was positively correlated to fatness, similar to findings from several studies in youth [15,16,17,18,21,26,29]. Moreover, a significant correlation between CRP and the clustered z-score was only found in the group with S4SF values above the median.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Therefore, the precise role of CRP in the development of CVD risk factors in humans remains unknown. In our study, CRP was positively correlated to fatness, similar to findings from several studies in youth [15,16,17,18,21,26,29]. Moreover, a significant correlation between CRP and the clustered z-score was only found in the group with S4SF values above the median.…”
Section: Discussionsupporting
confidence: 79%
“…CRP was not significantly correlated to VO 2peak after adjusting for S4SF. Other studies have found negative correlations between VO 2peak and CRP in youth [26,27,29,30]. Two of these studies found that the correlation was not significant after adjusting for fatness [27,30], like we did.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This is similar to findings in adults [16,29] and children [23], although in two of these studies no difference between high-fit and low-fit overweight individuals was observed, possibly due to poor measures of fatness and fitness [16] or low number (n = 4) of high-fit/overweight participants [23]. Similarly, girls with the same baseline adiposity level had lower longitudinal increase in CRP if baseline fitness was higher [42]. Unfortunately, no empirical classifications for fitness FFM exist.…”
Section: Discussionmentioning
confidence: 91%
“…However, Owen et al 22 , in the CHASE study, reported a strong association between PA measured objectively and CRP in a sample of Caucasian-European, Southern-Asiatic, and Afro-Caribbean children. While some studies with young subjects find negative associations between PA or cardiorespiratory fitness and CRP 2,22,23,24,25,26,27 , others do not 21,28,29,30,31,32,33,34,35,36 . Moreover, in many of these studies, the results are not presented independently from the body mass index (BMI), a potentially confounding variable of the relationship between CRP and PA or cardiorespiratory fitness 37 .…”
Section: Introductionmentioning
confidence: 99%